Zoomorficzne figurki Anubisa - Kwiatkowski, Karol (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2011)
Zoomorphic figurines of Anubis have usually comprised parts of larger objects such as coffins, shrines and canopic chests. The statuettes were made of wood, stone and sometimes of metal. Typology include three different postures of Anubis. This figurines symbolize a permanent care of the dead body or entrails, because Anubis was giving hope for resurrection and eternal life.
Anubis zoomorphic figurines